THE EFFECT OF LEARNING MODEL, LEARNING MEDIA AND SCHOOL STATUS TOWARD LEARNING OUTCOME OF BASKETBALL GAME - -, Arianto (The Journal of Educational Development, 2013)
The study aims to investigate the different effects of learning model, learning media and school status toward learning outcome of basketball game as well as the interaction between the observed variables. The study employed experimental method using factorial design 2x2x2. The population was 280 students with 96 male and female students as the sample. The data was analyzed using ANOVA and Turkey test α : 0,05. The results are: 1) Hypothesis 1 F count = 4,321   > F table 3,94     ( 2) Hypothesis 2,  F count 7,909 > F table  3,94   (3) F count 17, > F table 3,94   (4) F count 4,321> F table 3,94 (5) F count > F table    (6) F count 1,122< F table 3,94   (7) F count 4,321> F table 3,94